Yeast DNA polymerase ζ maintains consistent activity and mutagenicity across a wide range of physiological dNTP concentrations - Kochenova, Olga V. (Nucleic Acids Res, 2017)
In yeast, dNTP pools expand drastically during DNA damage response. We show that similar dNTP elevation occurs in strains, in which intrinsic replisome defects promote the participation of error-prone DNA polymerase ζ (Polζ) in replication of undamaged DNA. To understand the significance of dNTP pools increase for Polζ function, we studied the activity and fidelity of four-subunit Polζ (Polζ(4)) and Polζ(4)-Rev1 (Polζ(5)) complexes in vitro at ‘normal S-phase’ and ‘damage-response’ dNTP concentrations. The presence of Rev1 inhibited the activity of Polζ and greatly increased the rate of all three ‘X-dCTP’ mispairs, which Polζ(4) alone made extremely inefficiently. Both Polζ(4) and Polζ(5) were most promiscuous at G nucleotides and frequently generated multiple closely spaced sequence changes. Surprisingly, the shift from ‘S-phase’ to ‘damage-response’ dNTP levels only minimally affected the activity, fidelity and error specificity of Polζ complexes. Moreover, Polζ-dependent mutagenesis triggered by replisome defects or UV irradiation in vivo was not decreased when dNTP synthesis was suppressed by hydroxyurea, indicating that Polζ function does not require high dNTP levels. The results support a model wherein dNTP elevation is needed to facilitate non-mutagenic tolerance pathways, while Polζ synthesis represents a unique mechanism of rescuing stalled replication when dNTP supply is low.